Cyclometallated iridium complexes inducing paraptotic cell death like natural products: synthesis, structure and mechanistic aspects. Issue 38 (1st September 2016) - Tripathy, Suman Kumar; De, Umasankar; Dehury, Niranjan; Laha, Paltan; Panda, Manas Kumar; Kim, Hyung Sik; Patra, Srikanta
Abstract : Mononuclear cyclometallated iridium complexes of polypyridyl-phenazine based ligands have been synthesized and characterized which display excellent anticancer activity through paraptosis. Abstract : Six mononuclear Ir complexes (1–6 ) using polypyridyl-pyrazine based ligands (L1 andL2 ) and {[cp*IrCl(μ-Cl)]2 and [(ppy)2 Ir(μ-Cl)]2 } precursors have been synthesised and characterised. Complexes1–5 have shown potent anticancer activity against various human cancer cell lines (MCF-7, LNCap, Ishikawa, DU145, PC3 and SKOV3) while complex6 is found to be inactive. Flow cytometry studies have established that cellular accumulation of the complexes lies in the order2 >1 >5 >4 >3 >6 which is in accordance with their observed cytotoxicity. No changes in the expression of the proteins like PARP, caspase 9 and beclin-1, Atg12 discard apoptosis and autophagy, respectively. Overexpression of CHOP, activation of MAPKs (P38, JNK, and ERK) and massive cytoplasmic vacuolisation collectively suggest a paraptotic mode of cell death induced by proteasomal dysfunction as well as endoplasmic reticulum and mitochondrial stress. An intimate relationship between p53, ROS production and extent of cell death has also been established using p53 wild, null and mutant type cancer cells.